Cyclic Prime Graphicable Algebras - Lakshmi, R. Anantha; Jayalakshmi, K.; Madhavi, T. (Communications in Mathematics and Applications, 2022)
This study constitutes the continuation of innovative research in Discrete Mathematics introduced in earlier research on algebras, in general regarding the utilization of graphs to contemplate the specific instance of graphicable algebras, which form a subset of evolution algebras. Group theory, stochastic processes, and dynamical systems are all naturally linked to evolution algebras, which makes them extremely interesting. In light of a new line of research initiated previously by some of the authors, a depiction on primeness of a certain type of graphicable and subgraphicable algebra is given.